2022
DOI: 10.1002/ece3.8548
|View full text |Cite
|
Sign up to set email alerts
|

Life‐history traits and fitness of plateau pika (Ochotona curzoniae) in alpine meadow ecosystem

Abstract: Plateau pika (Ochotona curzoniae) is an endemic mammal living in the alpine meadow ecosystem in Qinghai–Tibet Plateau. We studied life history of plateau pika by mark–recapturing method. The research results showed that fitness of plateau pika to its habitat was lower than those of many other mammal species; plateau pika adopted quick growth strategy; the life‐history features of plateau pika were accorded with Charnov (Evolutionary Ecology Research, 2002, 4, 749)'s formula about life‐history classification, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…38 The multidimensional stereoscopic surveying technology proposed in this study improves the efficiency and reliability of the field work, does not harm the ecosystem, and provides a new way for the investigation and study of plateau pika activities on a large scale. In recent years, scholars have conducted a lot of work on the relationship between plateau pika activities and alpine grassland ecosystems, mainly using the number of pika holes to characterize the disturbance intensity, [39][40][41] and it was found that with the increase of the activities intensity, the vegetation coverage, vegetation height, the proportion of edible grass and aboveground biomass will continue to decrease, and the area of bald spots, weeds and poisonous plants will continue to increase, but the pika holes number will increase first and then decrease. [42][43][44] That is, the vegetation and soil conditions of the pika activities areas reflect the disturbance intensity objectively, and the intensity reflected by a single number of holes is not comprehensive.…”
Section: Discussionmentioning
confidence: 99%
“…38 The multidimensional stereoscopic surveying technology proposed in this study improves the efficiency and reliability of the field work, does not harm the ecosystem, and provides a new way for the investigation and study of plateau pika activities on a large scale. In recent years, scholars have conducted a lot of work on the relationship between plateau pika activities and alpine grassland ecosystems, mainly using the number of pika holes to characterize the disturbance intensity, [39][40][41] and it was found that with the increase of the activities intensity, the vegetation coverage, vegetation height, the proportion of edible grass and aboveground biomass will continue to decrease, and the area of bald spots, weeds and poisonous plants will continue to increase, but the pika holes number will increase first and then decrease. [42][43][44] That is, the vegetation and soil conditions of the pika activities areas reflect the disturbance intensity objectively, and the intensity reflected by a single number of holes is not comprehensive.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, rodents compete with livestock (e.g., yak and Tibetan sheep) for available vegetation (Harris et al, 2015; Yang & Jiang, 2002). Plateau pika, therefore, are considered to play a key role in food chains (Z. Guo et al, 2012; Lai & Smith, 2003; Smith & Foggin, 1999; Y. Zhang et al, 2016), although regarded as a harmful species (Chen et al, 2017; N. Fan et al, 1999; Pang & Guo, 2017; W. Wei et al, 2020), and have an adaptive strategy with a higher mortality and higher regeneration in its population (Nie et al, 2022). On the other hand, alpine creatures have to struggle with environmental and biological stresses through multilevel adaptations in the extreme environmental conditions of lower air temperature and lower atmospheric oxygen concentration (Dahal et al, 2020; Feijó et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Fan et al, 1999;Pang & Guo, 2017;W. Wei et al, 2020), and have an adaptive strategy with a higher mortality and higher regeneration in its population (Nie et al, 2022). On the other hand, alpine creatures have to struggle with environmental and biological stresses through multilevel adaptations in the extreme environmental conditions of lower air temperature and lower atmospheric oxygen concentration (Dahal et al, 2020;Feijó et al, 2020).…”
Section: Role Of Herbivores In Grassland Multifunctionmentioning
confidence: 99%
“…However, this species is regarded as a pest that leads to the degradation of the rangeland ecosystem in the QTP, and it has been largely eliminated by rodenticides [29,30]. Pikas are social mammals that live in groups of adults and their young in a family unit [31]. Within a population, these families consist of a variable number of adult breeding males and females, and individual families may exhibit monogamous, polygynous, or polyandrous mating systems [32].…”
Section: Introductionmentioning
confidence: 99%